Antithrombotic therapy in patients with acute coronary syndrome complicated by cardiogenic shock or out-of-hospital cardiac arrest: a joint position paper from the European Society of Cardiology (ESC) Working Group on Thrombosis, in association with the Acute Cardiovascular Care Association (ACCA) and European Association of Percutaneous Cardiovascular Interventions (EAPCI). Issue 2 (12th February 2020) - Gorog, Diana A; Price, Susanna; Sibbing, Dirk; Baumbach, Andreas; Capodanno, Davide; Gigante, Bruna; Halvorsen, Sigrun; Huber, Kurt; Lettino, Maddalena; Leonardi, Sergio; Morais, Joao; Rubboli, Andrea; et al.
Abstract: Timely and effective antithrombotic therapy is critical to improving outcome, including survival, in patients with acute coronary syndrome (ACS). Achieving effective platelet inhibition and anticoagulation, with minimal risk, is particularly important in high-risk ACS patients, especially those with cardiogenic shock (CS) or those successfully resuscitated following out-of-hospital cardiac arrest (OHCA), who have a 30-50% risk of death or a recurrent ischaemic event over the subsequent 30 days. There are unique challenges to achieving effective and safe antithrombotic treatment in this cohort of patients that are not encountered in most other ACS patients. This position paper focuses on patients presenting with CS or immediately post-OHCA, of presumed ischaemic aetiology, and examines issues related to thrombosis and bleeding risk. Both the physical and pharmacological impacts of CS, namely impaired drug absorption, metabolism, altered distribution and/or excretion, associated multiorgan failure, co-morbidities and co-administered treatments such as opiates, targeted temperature management, renal replacement therapy and circulatory or left ventricular assist devices, can have major impact on the effectiveness and safety of antithrombotic drugs. Careful attention to the choice of antithrombotic agent(s), route of administration, drug-drug interactions, therapeutic drug monitoring and factors that affect drug efficacy and safety, may reduce the risk of sub- or supra-therapeutic dosing and associated adverse events. This paper provides expert opinion, based on best available evidence, and consensus statements on optimising antithrombotic therapy in these very high-risk patients, in whom minimising the risk of thrombosis and bleeding is critical to improving outcome.